Postmodern Dönemde Kimliğin Belirleyicisi Olarak Tüketim [Tüketilmiş Kimlikler] / The Consumption as a Determination of Identity in The Postmodern Era [Consumed Identities] - Yavuz, Nihal; Zavalsız, Yusuf Sinan (Journal of History Culture and Art Research, 2015)
The Consumption as a Determination of Identity in The Postmodern Era [Consumed Identities] Abstract Technological developments which are increasing due to the production and product diversity have started to tempt people to consume rather than meeting their daily requirements. In this period, wherein hedonist approach became popular, people have created new life styles and producible – even reproducible – identities through consumption. The relationship between identity and consumption is one of the topics that need to be dealt with in recent years. This research will try to explain the effect of consumption habits on the formation of multiple and fragmented identities in the postmodern period. Consumption, which has started to direct human behaviors, has become now an identity indicator. As consumption is becoming influential on the formation of individuals’ identities, it is observed that symbolic values stand out in consumption habits. Identities have been exposed to consumption in today’s world where everything is being consumed fast. Postmodern Dönemde Kimliğin Belirleyicisi Olarak Tüketim [Tüketilmiş Kimlikler] Öz Teknolojik gelişmeye bağlı olarak artan üretim ve ürün çeşitliliği, insanların günlük ihtiyaçlarını karşılamanın ötesinde onları tüketime yönlendirmeye başlamıştır. Tüketimde hedonist anlayışın ön plana çıktığı bu dönemde insanlar, tüketim vasıtasıyla yeni yaşam tarzları ve üretilebilir hatta yeniden üretilebilir kimlikler oluşturmuştur. Günümüz postmodern toplumunda kimlik ve tüketim ilişkisi, üzerinde durulması gereken bir konudur. Bu araştırma, postmodern dönemdeki çoğul ve parçalanmış kimliklerin oluşumunda tüketim alışkanlıklarının etkisini açıklamaya çalışmaktadır. İnsan davranışlarına yön vermeye başlayan tüketim, artık bir kimlik göstergesi biçimini almıştır. Tüketim, bireylerin kimlik oluşumunda etkili olurken, tüketim alışkanlıklarında sembolik değerlerin ön plana çıktığı görülmektedir. Her şeyin hızla tüketildiği günümüz dünyasında artık kimlikler de tüketilir hale gelmiştir.